Philippine medical thesaurus on anatomy embryonic structures and urogenital system and diseases :pathological conditions, signs and symptoms in Bikol - Lanzuela, Andrew G. (2005)
The Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila teamed up for collaborative efforts in developing a Philippine Medical Thesaurus to address the need for a controlled vocabulary of medical terms. The first researches for the project were considered successful. In addition to the project the Philippine Medical Thesaurus on anatomy: Embryonic Structure and Urogenital System, and Diseases: Pathological conditions, signs and symptoms was done.